2014
DOI: 10.1002/pam.21763
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Rehabilitation and Counseling Services on the Labor Market Activity of Social Security Disability Insurance (SSDI) Beneficiaries

Abstract: We use data from a social experiment to estimate the impact of a rehabilitation and counseling program on the labor market activity of newly entitled Social Security Disability Insurance (SSDI) beneficiaries. Our results indicate that the program led to a 4.6 percentage point increase in the receipt of employment services within the first year following random assignment and a 5.1 percentage point increase in participation in the Social Security Administration's Ticket to Work program within the first three ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…A random assignment study of a job‐training program in the early 2000s finds that structured job counseling led to positive long‐run effects on reemployment rates for the most disadvantaged workers but not for others (Perez‐Johnson, Moore, & Santillano, ). Similarly, a study of Social Security Disability Insurance beneficiaries from 2007 to 2009 finds that those randomly assigned to receive medical care management and job‐counseling services had greater labor market success than those assigned to a control group that did not have such services (Weathers & Bailey, ).…”
Section: Introductionmentioning
confidence: 99%
“…A random assignment study of a job‐training program in the early 2000s finds that structured job counseling led to positive long‐run effects on reemployment rates for the most disadvantaged workers but not for others (Perez‐Johnson, Moore, & Santillano, ). Similarly, a study of Social Security Disability Insurance beneficiaries from 2007 to 2009 finds that those randomly assigned to receive medical care management and job‐counseling services had greater labor market success than those assigned to a control group that did not have such services (Weathers & Bailey, ).…”
Section: Introductionmentioning
confidence: 99%
“…Among AB Plus members who had any earnings (16%), average annual earnings were $10,187 during this period, about $2,300 more than the control group (a meaningful, but not statistically significant difference). The significant effects observed for the full AB Plus group were smaller and no longer statistically significant in Year 3, either due to SSA work disincentives, the end of program services, or worsening of beneficiaries’ health conditions (Michalopoulos et al, 2011; Weathers & Bailey, 2014). Findings for the 22% of the study sample with mental illness mirrored these patterns.…”
Section: Resultsmentioning
confidence: 94%
“…The Mental Health Treatment Study (MHTS) found employment support in combination with comprehensive health benefits, such as systematic medication management, led to a modest positive effect on earnings and a notable effect on reducing hospitalizations (Drake et al, 2016). The Accelerated Benefits (AB) demonstration found the provision of employment support services combined with health insurance to Social Security disability beneficiaries in the 2-year waiting period for Medicare increased earnings (Weathers & Bailey, 2014). In addition, health insurance sharply improved self-reported health among disability beneficiaries and led to a reduction in unmet medical needs (Weathers & Stegman, 2012).…”
Section: Discussionmentioning
confidence: 99%